Efisiensi Serbuk Kulit Jagung dan Kulit Bawang Merah Sebagai Adsorben dalam Menurunkan Kadar BOD dan COD pada Air Sungai - Sella Olivia Fitriani; Aussie Amalia (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The growth and development of industry around rivers has the potential to contribute large amounts of organic waste, namely BOD and COD. The determination of organic matter in water is carried out by measuring the amount of oxygen required in the water to break down the organic matter, either using microorganisms, chemicals or other methods. Adsorption using bioadsorbents can be used to overcome this problem, with bioadsorbents such as corn husks and shallot peels, which have a large surface area and are good at controlling organic substances that are not dissolved in water, making it more efficient to remove BOD and COD parameters. This research aims to analyse the ability of corn husk and shallot peel bioadsorbents to reduce the levels of BOD and COD parameters. In this research, river water from Mangetan Canal and bioadsorbent activated with 5% H3PO4 solution were used. The research results showed that the use of corn husk and shallot peel waste as adsorbent in a continuous adsorption process resulted in optimum percentage removal of BOD of 64.1%; COD of 72.5%; BOD of 73.3%; COD of 85% at 40 minutes contact time.